2010
DOI: 10.1155/2010/916525
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Milestones: A More Comprehensive Picture of Age-Appropriate Vaccination

Abstract: A challenge facing immunization registries is developing measures of childhood immunization coverage that contain more information for setting policy than present vaccine series up-to-date (UTD) rates. This study combined milestone analysis with provider encounter data to determine when children either do not receive indicated immunizations during medical encounters or fail to visit providers. Milestone analysis measures immunization status at key times between birth and age 2, when recommended immunizations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…7 Immunization records for study children were extracted from the ALERT Immunization Information System (IIS). IIS is a population-based data system capturing immunization doses administered by participating providers within a given area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Immunization records for study children were extracted from the ALERT Immunization Information System (IIS). IIS is a population-based data system capturing immunization doses administered by participating providers within a given area.…”
Section: Methodsmentioning
confidence: 99%
“…6 As an example, 1 recent US study found that 64.5% of undervaccination up to age 2 years was attributable to missed opportunities, whereas another recent study in India found that 79.6% of undervaccination up to age 6 years was related to missed opportunities. 7,8 One common type of missed opportunity is when a child presents sick when shots are due, with the added possibility that the sick visit will take the place of a routine or wellbaby visit. 9 This problem has long been recognized as among the more difficult barriers to address, and it can account for the majority of true missed opportunities at a practice.…”
mentioning
confidence: 99%
“…Utilization of vaccination services is dependent on sociodemographic factors of the target population, as well as the number of health workers and availability of safe needles and syringes (5). Two studies show that children missed immunizations due to the provider's reluctance to vaccinate children while sick or when visiting health care centres for other purposes (9,28). This study did not focus on these provider risk factors.…”
Section: Source Of Epi Informationmentioning
confidence: 99%
“…[6][7][8][9][10][11] Although several published alternative schedules exist, [12][13][14] studies have shown that most parents who admit not using the routine schedule opt for a more individualized alternative schedule approach often developed with friends or their pediatrician. 9,[15][16][17][18][19] Children who were under-vaccinated in a large group of managed care organizations were found to follow almost 1400 individualized vaccination patterns. 16 Despite this variability, 3 specific tactics associated with alternative schedules have emerged: delay of vaccines or particular doses (not because of unavailability or illness), selective refusal of specific vaccines, and a reduction in the number of vaccines given at each visit.…”
mentioning
confidence: 99%